Handbook of Florida Fence and Property Law: Background and Definitions - Michael T. Olexa; Jeffrey Van Treese; Christopher A. Hill (EDIS)
This information is included in the Handbook of Florida Fence and Property Law, Circular 1242. Of interest to farmers and farmland owners in particular, this handbook is designed to inform property owners of their rights and responsibilities in terms of their duty to fence. Discussed areas include a property owner’s responsibility to fence when livestock is kept on the property, the rights of adjoining landowners to fence, the placement of fences, encroachments, boundary lines, easements, contracts, nuisances, and a landowner’s responsibilities towards persons who enter his property.